Web systems quality evolution - Rio, A; Abreu, F. B. e (2016 10th International Conference on the Quality of Information and Communications Technology (QUATIC), 2016)
Software evolution is a well-established research area, but not in the area of web systems/applications. Web projects are normally more complex than other software development projects because they have both server and client code, encompass a variety of programming languages, and are multidisciplinary. We aim to produce a catalog of web smells to help avoiding the problems in web development code before they happen, thus saving time and reducing cost. By means of longitudinal studies we plan to analyze the impact of these web smells in web systems maintainability and reliability. This will require developing a tool to detect the proposed web smells. For validation sake, we will also use surveys among web systems developers and peer reviewing in academic fora.